Camalig de Morong a visitor learning center for sustainable tourism and disaster mitigation - Castillo, Ariane M.; De Chavez, Kelvin (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Endowed with an abundance of picturesque landscapes and seascapes, the Philippines is a dream destination for tourists. Our nature-rich country is one of the 18 mega-biodiverse countries of the world. We rank fifth in the most number of plant species. The title of the fifth longest coastline in the world belongs to us, giving home of a wide array of marine biodiversity. The global trend in tourism recorded an increasing number of tourists interested with environmental sites. Travelers now seek to go to the most remote places, those closer to forests and untapped marine spots. This is why Philippine tourism grew steadily. The steady growth of tourism industry has prompted the Philippine Department of Tourism to focus on eco-tourism, a form of sustainable tourism which involves the responsible travel to natural areas and promotes the conservation of natural environment and the well-being of the locals, as part of the economic development plans. The Philippines, home to an abundance of ecotourism sites, is particularly famous for Palawan and Boracay. These two islands shelter diverse biosystems, breathtaking sceneries and extensive outdoor activities.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Tourism -- Philippines